THE IMPLEMENTATION OF SELF-REGULATED LEARNING (SRL) STRATEGIES THROUGH YOUTUBE TO LEARN GRAMMAR: THE IMPLEMENTATION OF SELF-REGULATED LEARNING (SRL) STRATEGIES THROUGH YOUTUBE TO LEARN GRAMMAR - Ria, Ade; Susilawati, Endang; Rahmani, Eka Fajar (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study employed a case study design with qualitative approach to identify the process of Self-Regulated Learning (SRL) by participants successful in learning English grammar. The researcher did a pre-survey to choose participants through Google Form. The researcher interviewed participants by in-depth interview to identify the process of Self-Regulated Learning (SRL) could make participants successful in learning English grammar. Learners are interested in learning English grammar through YouTube because YouTube provides a lot of videos to learn grammar so, YouTube videos could be an effective tool in learning grammar by implementing Self-Regulated Learning (SRL). The results of this research showed that participants have successfully learned grammar by applying Self-Regulated Learning (SRL) and following several stages such as; goal setting, planning, monitoring progress and self evaluation. The participants easily wrote spontaneously the rules of grammar related to the learning material so, the participants got an A score in the Essay Writing course. The results of participants writing were an effective implementation in improving understanding and application of grammar rules. Keyword : Self-Regulated Learning (SRL), YouTube, Learning grammar.